Readmission Mortality After TAVR: The Combined Effect of Teaching Hospital Status and Cause of Readmission - Carlos E. Diaz-Castrillon, MD; Dustin Kliner, MD; Derek Serna-Gallegos, MD; Catalin Toma, MD; AJ Conrad Smith, MD; Hemal Gada, MD; Amber Makani, MD; Irsa Hasan, MD; Takuya Ogami, MD; Yisi Wang, MPH; Ibrahim Sultan, MD (CJC Open)
Background: Variability in transcatheter aortic valve replacement (TAVR) readmission rates highlights the importance of assessing post-discharge outcomes. Understanding how teaching hospital status and causes of readmission influence mortality could optimise post-TAVR care. Methods: Using the National Readmissions Database, we identified 155,298 TAVR admissions from 2012 to 2020. We evaluated the interaction effect between teaching status and cause of readmission on readmission-related mortality through adjusted mixed-effects models. Results: Overall, 18.9% of patients (n = 29,479) had a nonelective readmission within 90 days, with no significant difference between teaching and nonteaching hospitals (19.3% vs 18.9%; P > 0.05). Cardiac-related readmissions accounted for 42.7% of cases, while noncardiac readmissions made up 57.3%, with no differences observed in their distribution between teaching and nonteaching hospitals. The unadjusted 90-day readmission mortality rate was 3.8%, without significant differences between teaching and nonteaching hospitals (3.8% vs 4.1%; P = 0.38). A downward trend in nonelective readmission and readmission-related mortality rates was observed, regardless of teaching status. An interaction effect between teaching status and the cause of readmission was identified: Noncardiac readmissions to teaching hospitals were associated with increased odds of death (odds ratio [OR] 1.82, 95% confidence interval [CI] 1.59-2.07; P < 0.001) compared with nonteaching hospitals, whereas cardiac readmissions to teaching hospitals were associated with decreased odds of in-hospital mortality (OR 0.55, 95% CI 0.48-0.62; P < 0.001). Conclusion: Our findings indicate a differential association between teaching hospital status and 90-day readmission mortality, contingent on the cause of readmission. Further research, including the use of metrics such as failure to rescue, is needed to better understand the relationship between patient-level variables and teaching hospital status. Résumé: Contexte: La variabilité des taux de réadmission pour un remplacement valvulaire aortique par cathéter (RVAC) souligne l'importance d'évaluer les résultats cliniques après la sortie de l'hôpital. Comprendre comment le statut d'hôpital universitaire avec fonction d'enseignement et les causes de réadmission influencent la mortalité pourrait optimiser les soins post-RVAC. Méthodes: En utilisant la base de données nationale des réadmissions (NRD), nous avons identifié 155 298 admissions pour RVAC de 2012 à 2020. Nous avons évalué l'effet d'interaction entre le statut d'hôpital universitaire et la cause de la réadmission sur la mortalité liée à la réadmission au moyen de modèles à effets mixtes ajustés. Résultats: Dans l'ensemble, 18,9 % des patients (n = 29 479) ont subi une réadmission non programmée dans les 90 jours, sans différence significative entre les hôpitaux universitaires et non universitaires (19,3 % vs 18,9 % ; p > 0,05). Les réadmissions pour cause cardiaque représentaient 42,7 % des cas, tandis que les réadmissions pour cause non cardiaque représentaient 57,3 %, sans qu'aucune différence n'ait été observée dans leur répartition entre les hôpitaux universitaires et les hôpitaux non universitaires. Le taux de mortalité non ajusté, à 90 jours, suite à une réadmission, était de 3,8 %, sans différence significative entre les hôpitaux universitaires et non universitaires (3,8 % vs 4,1 % ; p = 0,38). Une tendance à la baisse des taux de réadmission non planifiée et de mortalité liée à la réadmission a été observée, quel que soit le statut de l'hôpital. Un effet d'interaction entre le statut de l'hôpital et la cause de la réadmission a été identifié : les réadmissions non cardiaques dans les hôpitaux universitaires étaient associées à une augmentation du risque de décès (rapport de cotes [RC] 1,82, intervalle de confiance [IC] à 95 % 1,59-2,07 ; p < 0,001) par rapport aux hôpitaux non universitaires, tandis que les réadmissions cardiaques dans les hôpitaux universitaires étaient associées à une diminution du risque de mortalité à l'hôpital (RC 0,55, IC à 95 % 0,48-0,62 ; p < 0,001). Conclusion: Nos résultats indiquent une association différentielle entre le statut d'hôpital universitaire et la mortalité à 90 jours, en fonction de la cause de la réadmission. D'autres recherches, y compris l'utilisation de mesures telles que l'échec des interventions de sauvetage, sont nécessaires pour mieux comprendre la relation entre les variables au niveau des patients et le statut d'hôpital universitaire.